SOLIDARITY EXPRESSIONS EMERGED IN ADDRESSING SYSTEM AS LINGUISTIC SIGNAL - Agung, Winantu Kurnianingtyas Sria (Pusat Pengembangan Bahasa, 2016)
Language has the particular roles relevant to the situation and eventwhen the communication holds. In taking a part into a communication,the speaker must understand in what context they speak whether hespeaks in formal or informal context. Moreover, the role-relationshipbetween the speaker and hearer, for instance, the communicationbetween parents to children, a boss and his employee. Then, the settingof the communication, for example, at home, offce, market, etc alsobecomes the major factors in conducting communication. Languageallows community not only to communicate with others but alsoto establish personal identity among individuals and communities.The social class or social stratifcation exists in the term of powerand solidarity. The existence of power and solidarity reï¬ects in theway people communicate with others and it can be seen through thelanguage they use.